Small Arms and Light Weapons Proliferation: Implications for Sahel Regional Security - Tamunopubo Big Alabo; Adokiye Big Alabo (East Asian Journal of Multidisciplinary Research, 2023)
The study examined small arms and light weapons proliferation and its implications for Sahel regional security. The study adopted institutional theory propounded by Meyer John and Rowen Brian. It adopted Ex-post facto research design, data for the study were sourced through secondary sources and analyzed using content analysis. The study discovered that the Sahel region's porous borders make it simple for illicit traffickers to smuggle small arms and light weapons because transnational criminal organisations and armed groups are very mobile in uncontrolled border regions. The study recommended among others that; states in the region should intensify efforts towards strict monitoring and management of local illicit manufacturing of firearms.